Interventional therapies for malignant pleural effusions: The present and the future. Issue 6 (19th June 2014) - Thomas, Rajesh; Francis, Roslyn; Davies, Helen E.; Lee, Y.C. Gary
Abstract The approach to management of malignant pleural effusions (MPE) has changed over the past few decades. The key goals of MPE management are to relieve patient symptoms using the least invasive means and in the most cost‐effective manner. There is now a realization that patient‐reported outcome measures should be the primary goal of MPE treatment, and this now is the focus in most clinical trials. Efforts to minimize patient morbidity are complemented by development of less invasive treatments that have mostly replaced the more aggressive surgical approaches of the past. Therapeutic thoracentesis is simple, effective and generally safe, although its benefits may only be temporary. Pleurodesis is the conventional and for a long time the only definitive therapy available. However, the efficacy and safety of talc pleurodesis has been challenged. Indwelling pleural catheter (IPC) drainage is increasingly accepted worldwide and represents a new concept to improve symptoms without necessarily generating pleural symphysis. Recent studies support the effectiveness of IPC treatment and provide reassurance regarding its safety. An unprecedented number of clinical trials are now underway to improve various aspects of MPE care. However, choosing an optimal intervention for MPE in an individual patient remains a challenge due to our limited understanding of the underlying pathophysiology of breathlessness in MPE and a lack of predictors of survival and pleurodesis outcome. This review provides an overview of common pleural interventional procedures used for MPE management, controversies and limitations of current practice, and areas of research most needed to improve practice in future.